Exercise Protects Against Defective Insulin Signaling and Insulin Resistance of Glucose Transport in Skeletal Muscle of Angiotensin II-Infused Rat - Surapongchai, Juthamard; Rattanavichit, Yupaporn; Buniam, Jariya; Saengsirisuwan, Vitoon (Frontiers in Physiology, 2018)
Objectives: The present study investigated the impact of voluntary exercise on insulin-stimulated glucose transport and the protein expression and phosphorylation status of the signaling molecules known to be involved in the glucose transport process in the soleus muscle as well as other cardiometabolic risks in a rat model with insulin resistance syndrome induced by chronic angiotensin II (ANGII) infusion. Materials and Methods: Male Sprague-Dawley rats were assigned to sedentary or voluntary wheel running (VWR) groups. Following a 6-week period, rats in each group were subdivided and subcutaneously administered either normal saline or ANGII at 100 ng/kg/min for 14 days. Blood pressure, glucose tolerance, insulin-stimulated glucose transport and signaling proteins, including insulin receptor (IR), insulin receptor substrate 1 (IRS-1), Akt, Akt substrate of 160 kDa (AS160), AMPKα, c-Jun NH2-terminal kinase (JNK), p38 MAPK, angiotensin converting enzyme (ACE), ANGII type 1 receptor (AT1R), ACE2, Mas receptor (MasR) and oxidative stress marker in the soleus muscle, were evaluated. Results: Exercise protected against the insulin resistance of glucose transport and defective insulin signaling molecules in the soleus muscle; this effect was associated with a significant increase in AMPK Thr172 (43%) and decreases in oxidative stress marker (31%) and insulin-induced p38 MAPK Thr180/Tyr182 (45%) and SAPK/JNK Thr183/Tyr185 (25%), without significant changes in expression of AT1R, AT2R, ACE, ACE2 and MasR when compared to the sedentary rats given ANGII infusion. At the systemic level, VWR significantly decreased body weight, fat weight, and systolic blood pressure as well as improved serum lipid profiles. Conclusion: Voluntary exercise can alleviate insulin resistance of glucose transport and impaired insulin signaling molecules in the soleus muscle and improve whole-body insulin sensitivity in rats chronically administered with ANGII.